GENETIC VARIABILITY, HERITABILITY AND GENETIC ADVANCE FOR YIELD COMPONENT AND QUALITY TRAITS IN SPRING WHEAT (TRITICUM AESTIVUM L.) - DINESH KUMAR; S. A. KERKHI (The Bioscan, 2015)
A field study was carried out involving 10 parents and 45 F 1 ’s planted in RBD having three replications during 2011-2012. The analysis of genetic variability, heritability and genetic advance for fourteen quantitative traits viz., days to 50% flowering, days to maturity, number of productive tillers/ plant, plant height, flag leaf area, spike length, spikelets/ spike, grains/ spike, 1000-grain weight, biological yield/ plant, grain yield/ plant, harvest index, ash content and gluten content. The maximum values of pcv and gcv were recorded for flag leaf area, while the minimum for days to maturity. High heritability coupled with high genetic advance was observed for flag leaf area, grain yield/ plant and biological yield/ plant. The high heritability coupled with moderate genetic advance for grains/ spike, number of productive tillers/ plant, plant height, ash content and spike length were recorded while for traits like 1000-grain weight, days to 50% flowering, gluten content, spikelets/ spike and days to maturity high heritability coupled with low genetic advance was observed.